POWER GENERATION BY DIFFUSER AUGMENTED WIND TURBINE - Gade Sagar; Ramsagar Kalyankar; Pankaj Chikhale (International Journal of Innovations in Engineering Research and Technology, 2021)
Brimmed diffuser is collection–acceleration device which shrouds a wind turbine.For a given turbine diameter, the power augmentation can be achieved by brimmed diffuser, popularly known as wind lens. The present numerical investigation deals with the effect of low pressure region created by wind lens and hence to analyze the strong vortices formed by a brim attached to the shroud diffuser at exit. Also in this analysis, a comparative numerical prediction of mass flow rates through the wind turbine has been carried out with various types of wind lens which in turn helps to optimize the torque augmentation. It has been numerically proved that there is significant increase in the wake formation & vortex strength when brimming effect is added to a diffuser